Handbook of analytical techniques in concrete science and technology (Noyes Publications William Andrew Pub., 2001)
Measuring the long-term durability of new types of concrete and concrete technologies is important to their acceptance in the marketplace. This handbook of analytical techniques provides a reference to the procedures used to test today's materials. Ranging from chemical and thermal analysis, to IR and Nuclear Magnetic Resonance spectroscopy, to Scanning Electron Microscopy, x-ray diffraction, computer modeling and more, the book provides first-hand explanations of modern methods. It includes many analytic techniques, applied to a wide range of organic, inorganic, and composite materials and additives